2020
DOI: 10.1016/j.physletb.2020.135216
|View full text |Cite
|
Sign up to set email alerts
|

Holographic p-wave superfluid in the AdS soliton background with RF2 corrections

Abstract: We investigate the holographic p-wave superfluid in the background metric of the AdS soliton with RF 2 corrections. Two models, namely, the Maxwell complex vector field model and Yang-Mills theory, are studied in the above context by employing the Sturm-Liouville approach as well as the shooting method. When turning on the spatial components of the gauge field, one observes that, in the probe limit, the inclusion of RF 2 corrections hinders the superfluid phase transition. On the other hand, however, in the ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Thus, as discussed in Refs. [18,29,30], we have to impose an additional Neumann boundary condition F ′ (0) = 0 for the operator O 1 but need not impose any restrictions on F ′ (z) for the operator O 2 .…”
Section: A Critical Chemical Potentialmentioning
confidence: 99%
“…Thus, as discussed in Refs. [18,29,30], we have to impose an additional Neumann boundary condition F ′ (0) = 0 for the operator O 1 but need not impose any restrictions on F ′ (z) for the operator O 2 .…”
Section: A Critical Chemical Potentialmentioning
confidence: 99%
“…Thus, we have to impose the Neumann boundary condition F ′ (0) = 0 for the operator O − , just as analyzed in Refs. [21,53,57,62].…”
Section: Critical Chemical Potentialmentioning
confidence: 99%
“…For the ground state, Nishioka et al showed that the soliton becomes unstable to form scalar hair and a second order phase transition can happen when the chemical potential is sufficiently large beyond a critical value µ c , which can be used to describe the transition between the insulator and superconductor [24]. This pioneering work has led to many investigations concerning the s-wave [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], p-wave [45][46][47][48][49][50][51][52][53][54] and s+p [55] holographic insulator/superconductor phase transition with the ground state. Interestingly, taking advantage of the Sturm-Liouville method first proposed by Siopsis and Therrien [56], Li studied the holographic insulator/superconductor phase transition analytically and obtained not only the ground state of the phase transition but also the first excited state in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the new holographic p-wave model [9], the authors using charged complex vectors, which are also known as Proca fields, to extend the holographic p-wave superfluid model to more general values of the charge and the mass parameters. Therefore a lot of study emerge to consider the more general p-wave superfluid in various setups [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Further investigations also involve in both the s-wave and p-wave orders together to study the competition and coexistence between the two different orders in holography [24][25][26][27][28][29][30][31][32][33]36].…”
Section: Introductionmentioning
confidence: 99%